Implementasi Kebijakan Pengembangan Pariwisata Berkelanjutan Pada Dinas Pemuda, Olahraga Dan Pariwisata Kabupaten Sekadau - Sinlilika Sinlilika; Yulius Yohanes; Arifin Arifin (Jurnal Multidisiplin Dehasen (MUDE), 2026)
The problems in this research stem from the lack of communication between Sekadau Regency government officials and the community, limited resources, weak disposition or attitude of implementers, and the unavailability of SOPs for developing tourist attractions. The aim of this research is to describe and analyze communication, disposition, resource and bureaucratic structure factors in the implementation of tourism development policies on the potential community-based natural tourist attraction of Air Terjun Batu jato National Park in Taman District, Sekadau Regency. This research uses descriptive research methods with a qualitative approach. The results of this research indicate that the implementation of communication in the context of developing the community-based natural tourist attraction of Air Terjun Batu jato National Park in Taman District, Sekadau Regency has not been running effectively, seen as the transmission or distribution of communication is not accurate, the clarity of information is still lacking, and the consistency of policy implementation is weak. . The disposition or attitude of the implementer has not been fully implemented. The resources available for developing tourist attractions are still limited, both in terms of the adequacy of implementing staff, the availability of information which is still minimal, the authority which is still limited and the availability of facilities. Then the implementation of the bureaucratic structure for policy implementation does not yet have a Standard Operational Procedure (SOP), and fragmentation is weak. Suggestions or recommendations in order to improve the implementation of communication, disposition, resources and bureaucratic structure, it is necessary to transmit accurate information, accuracy of information, consistency with orders, placement of appropriate personnel, increase incentives, increase the number of staff, information in policy implementation, authority formal ones, supporting facilities, creating SOP and the need for coordination in order to overcome fragmentation.